Analysis Of Good Manufacturing Practices (GMP) Training Information System Design Using Extreme Programming (XP) Methods - Sinlae, Fried; Yasir, Muhammad (Siber Journal of Advanced Multidisciplinary, 2024)
This research is about the Good Manufacturing Practices (GMP) Training Information System. Apart from that, the author is trying to carry out an analysis of the design of the Good Manufacturing Practices (GMP) information system. The aim is to carry out tests to reduce problems that exist at the research site, PT employee tools. XYZ for training and GMP tests as well as getting the final results of the GMP tests carried out by employees. The method used in the research is literature study, interviews and observation. The results of this research show that system quality can make it easier to carry out GMP training. So it can be concluded that the resulting value still shows the suitability of the system to be implemented in accordance with the real system.